Stale forward guidance - Gunda-Alexandra Detmers; Dieter Nautz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
An increasing number of central banks manage market expectations via interest rate projections. Typically, those projections are updated only quarterly and thus, may become stale when new information enters the market. We use data from New Zealand to investigate the time-varying and state-dependent effects of interest rate projections on market expectations and interest rate uncertainty. Confirming the stabilizing effect of fresh central bank announcements, we show that interest rate uncertainty rises between two projection releases. Moreover, rate uncertainty and the importance of macroeconomic news increase if expectations deviate from the rate projected by the central bank. Counterfactual analysis suggests that the efficiency of projections would improve if the central bank updated its projection whenever it becomes stale.
Keywords: E52; E58; 330; Central bank interest rate projections; central bank communication; quantitative forward guidance; interest rate uncertainty